2016
DOI: 10.1158/0008-5472.can-16-0399
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Weight Loss and Exercise Effects on Serum Biomarkers of Angiogenesis in Overweight Postmenopausal Women: A Randomized Controlled Trial

Abstract: Obese and sedentary persons have an increased risk for cancer, but underlying mechanisms are poorly understood. Angiogenesis is common to adipose tissue formation and remodeling, and to tumor vascularization. 439 overweight/obese, healthy, postmenopausal women (body mass index (BMI)>25 kg/m2) aged 50-75 years, recruited between 2005-2008 were randomized to a 4-arm 12-month randomized controlled trial, comparing a caloric restriction diet arm (goal: 10% weight-loss, N=118), aerobic exercise arm (225 min/week of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…There was a statistically significant linear trend of reductions in PEDF and VEGF with increasing weight loss among participants randomized to both the diet and diet+exercise arm (all P trend <0.0001). Participants randomized to the exercise arm also had statistically significant linear trend of reductions in PEDF with increasing levels of weight loss (12)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There was a statistically significant linear trend of reductions in PEDF and VEGF with increasing weight loss among participants randomized to both the diet and diet+exercise arm (all P trend <0.0001). Participants randomized to the exercise arm also had statistically significant linear trend of reductions in PEDF with increasing levels of weight loss (12)…”
Section: Resultsmentioning
confidence: 99%
“…In our prior studies of the impact of weight loss on reducing levels of circulating biomarkers of angiogenesis (10,12), we discussed the potential utility of weight loss as a chemopreventive approach targeting both angiogenesis and inflammation in healthy individuals. (35) Again, while it is currently impossible to ascertain whether reductions in circulating levels of angiogenic factors might inhibit tumor cell growth and progression by blocking the vascularization of indolent tumors, the long-term maintenance of reduced levels of VEGF and PEDF can only reflect a more beneficial angiogenic profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Weight loss surgery has become the most popular method to treat morbidly obese patients because it has substantial beneficial associations with weight loss and several clinical outcomes [18]. The recent studies showed that obesity-associated weight loss via diet contributed to the reduction in some circulating levels of positive regulators of angiogenesis [19,20], depending on the extent of weight loss [19]. Other authors demonstrated that PDGF-B-PDGFRβ signaling regulates adipose tissue expansion and glucose metabolism via vascular remodeling in an animal model of diet-induced obesity [5].…”
Section: Discussionmentioning
confidence: 99%